Respuesta :

x=23

Simplifying

(3x + -50) + (7x)

Reorder the terms:

(-50 + 3x) + (7x)

Remove parenthesis around (-50 + 3x)

-50 + 3x + (7x) =

Combine like terms: 3x + (7x)

-50 + 10x

Solving

-50 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '50' to each side of the equation.

-50 + 50 + 10x = 180 + 50

Combine like terms: -50 + 50 = 0

0 + 10x = 180 + 50

10x = 180 + 50

Combine like terms: 180 + 50 = 230

10x = 230

Divide each side by '10'.

Simplifying

x = 23